Analisa perbandingan kekuatan hasil pengelasan TIG dan pengelasan MIG pada Aluminium 5083 - Iswanto Iswanto; Noerdianto Noerdianto; A’rasy Fachruddin; Mulyadi Mulyadi (Universitas Muhammadiyah Metro, 2020)
This paper will discuss the comparative strength of TIG (Tungsten Inert Gas) welding results and MIG (Metal Inert Gas) welding results. Welding is carried out on aluminium material 5083, by varying the amount of amperage in each type of welding. Amperes variations used in TIG welding and MIG welding are 130 Amperes, 140 Amperes , and 150 Amperes. Furthermore, testing is carried out to determine the strength of the welding results, namely by bending and tensile test. From the bending test results obtained the highest bending strength of 262.36 kgf/mm2, obtained at MIG welding with a strong current used 130 Amperes. The lowest bending strength of 21.61 kgf/mm2, is obtained in TIG welding with the strong current used by 130 Amperes. From the tensile test results obtained the highest tensile strength of 23.48 kgf/mm2, obtained at MIG welding with a strong current used 130 Amperes. The lowest tensile strength of 17.41 kgf/mm2, obtained at TIG welding with a strong current used 130 Amperes.Keywords: TIG welding, MIG welding, Aluminium 5083.